Climate change enhances soil fauna population and biomass in grasslands of the Loess Plateau - Xi Yang; Ming’an Shao; Tongchuan Li (Communications Earth & Environment)
Abstract Soil fauna is a crucial component of soil biodiversity, which affects various processes and functions in terrestrial ecosystems. However, few quantitative, large-scale spatially distributional studies have explored the abundance and biomass of soil fauna. In this study, the 95 areas at 19 sites in the Loess Plateau region were surveyed. Numerous individual samples of soil fauna and environmental factors such as climate, soil and vegetation on which soil fauna depended were collected and identified. The results indicate that the soil fauna of the Loess Plateau grassland can be classified into 3 phyla, 10 classes and 23 orders, with an average soil fauna density of about 2 × 104 ind. m−2, and an average biomass of about 18 g m−2. Notably, the soil fauna density and biomass decreased significantly as the latitude increased, and the overall spatial distribution pattern revealed a gradual decrease from southeast to northwest in the Loess Plateau. We found that climatic factors, especially precipitation, primarily drove the spatial distribution of soil fauna density and biomass, contributing 72% and 58%, respectively. Conservatively estimated, the number of soil fauna on the Loess Plateau exceeds 4 × 1015, with the estimated total biomass of 4 × 106 t, equivalent to 2 Mt carbon. In addition, model predictions indicate that soil fauna populations and biomass of grassland in the Loess Plateau increased 27% and 29%, from 2000 to 2022. This study highlights major ecological and geographical gaps in the current knowledge of soil fauna, provides ideas for enhancing the accuracy of global soil fauna biomass assessments, and presents new perspectives to guide further investigations into the precise contribution of soil fauna to the soil carbon cycling.